Exploring teacher adoption, adaptation, and implementation of a daily report card intervention when using the daily report card online platform - Owens, Julie Sarno; Lee, Mary; Eackles, Kelsey; Medina, Dassiell; Evans, Steven W.; Reid, Jacob (Frontiers in Education, 2022)
Technology-based supports offer promise for helping elementary school teachers implement Tier 2 interventions to address challenging student behavior. The Daily Report Card Online (DRCO) platform is a cloud-based web application designed to support teachers’ adoption and implementation of a high-quality daily report card (DRC) intervention through the use of professional development resources, guided intervention design workflows, algorithm-based decision-making tools, and real-time progress monitoring. We examined teacher adoption, adaptation, and implementation of a DRC intervention when using the DRCO platform with support from a consultant during the 2021–2022 school year. Participants were 29 teachers, 20 of whom used the DRCO to implement a DRC with a student (n = 20). The most frequently chosen target behaviors were student interruptions, non-compliance, and work completion. When using the DRCO platform, teachers achieved several procedures that align with evidence-based guidelines (e.g., screening, baseline tracking, setting achievable goals, tracking behaviors over time). However, goal criterion changes and shaping procedures were used less often than expected. Despite the option to track behaviors solely with technology, 60% of teachers tracked student behaviors via paper methods (e.g., printed the DRC card, used sticky notes). Adaptations were made by 40% teachers; however, all adaptations involved modifying printed materials to be more student-friendly (e.g., add clipart to the DRC) and did not change the guiding principles of the intervention. Tau-effect sizes for academic and behavioral target behaviors on the DRC showed small to moderate change over time and change in target behaviors showed some association with change in global teacher ratings. Lastly, we identified associations between teacher characteristics and adoption and implementation, as well as associations between implementation and student outcomes.